Linking smallholders to livestock markets: Combining market and household survey data in Tanzania - Pica-Ciamarra, U.; Baker, Derek; Chassama, J.; Fadiga, M.L.; Nsiima, L. (2011)
Linking farmers to markets is widely viewed as a milestone towards promoting economic growth and poverty reduction. However, market and institutional imperfections along the supply chain thwart perfect vertical and spatial price transmission and prevent farmers and market actors from getting access to information, identifying business opportunities and allocating their resources efficiently. This acts as a barrier to market-led rural development and poverty reduction. This paper reviews and analyses household information, and the major livestock market and marketing data available in Tanzania, in relation to market-led development possibilities. Household-level data collected by the Tanzania National Bureau of Statistics and market data collected and disseminated by the Livestock Information and Knowledge System of the Tanzania Ministry of Industry and Trade are reviewed and utilised together. Both types of data help identify market opportunities for livestock producers, but only their joint use could provide policy makers with the information needed to design and implement policies that facilitate access to markets for livestock producers. Options to promote integration of household-level data and market data are discussed, which would facilitate the implementation of the Tanzania Statistical Master Plan and contribute to the implementation of the Global Strategy to Improve Agricultural and Rural Statistics